A interdisciplinaridade como paradigma nos contextos de cursos de licenciatura em filosofia em duas instituições de ensino superior do sul do Brasil - Mazzonetto, Clenio Vianei (Universidade do Vale do Rio dos Sinos, 2020)
This thesis has as its theme interdisciplinarity and its expressions in the contexts of educational policies for teacher education and undergraduate courses in Philosophy. It discusses the possibilities and limits for an interdisciplinary paradigm in education, within the scope of teacher education policies and in the pedagogical proposals of undergraduate courses in Philosophy in two higher education institutions in the Southern Region of Brazil. It deals with modern rationality subscribed to subjectivity based on the Cartesian cogito, the subjective consciousness of the subject that operates as a unifying projection of knowledge and the determination of truth as certainty of reason. From the mid-twentieth century onwards, interdisciplinarity began to be discussed as a possibility of overcoming educational deficits and the way of building knowledge, produced by the previous paradigm, overcoming fragmented subjective rationality. This thesis discussed, through the interdisciplinary paradigm, the possibility of building knowledge, as well as teacher training, so that they can be contemplated with dialogue, intersubjectivity, interrelationships and multi-knowledge, so that, in this way, a process of holistic education is contemplated. The general objective was to analyze possibilities and limits of the operationalization of the interdisciplinary paradigm in education, within the horizon of teacher training policies (PIBID and PARFOR) and in the pedagogical proposals of undergraduate courses at the University of Passo Fundo (UPF) and the Federal University of Fronteira Sul (UFFS) - Chapecó Campus. This investigation is supported, methodologically, in the qualitative approach in the light of the dialectic-hermeneutics for the understanding of the studied object. For the construction of the results, a documentary analysis of the Political Projects of the Degree Programs in Philosophy of the universities in question was necessary, as well as, semi-structured interviews were conducted, in group, with the professors that make up the collegiate of the Degree courses in Philosophy of the institutions researched and submitted to content analysis. In the administrative and pedagogical dimensions, the policies of PIBID and PARFOR, in the PPCs of the courses, signal the possibilities of carrying out activities articulated to meet the interdisciplinary paradigm. The professors pointed out that there are some limits in the operationalization of interdisciplinarity, but, on the other hand, they demonstrated that actions take place that meet the interdisciplinary paradigm in the Philosophy Degree courses. Therefore, it is considered that the knowledge constructed in this investigation can contribute to expand the discussions and implementation of the interdisciplinary paradigm.
Keywords: Paradigma interdisciplinar; Interdisciplinaridade na educação; Políticas de formação docente; Racionalidade moderna; Intersubjetividade na educação; Interdisciplinary paradigm; Interdisciplinarity in education; Teacher training policies; Modern rationality; Intersubjectivity in education; ACCNPQ::Ciências Humanas::Educação